2021
DOI: 10.1038/s41598-021-88859-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new mammal species (Soricidae: Eulipotyphla) from Narcondam volcanic island, India

Abstract: We discovered a new Crocidura species of shrew (Soricidae: Eulipotyphla) from Narcondam Island, India by using both morphological and molecular approaches. The new species, Crocidura narcondamica sp. nov. is of medium size (head and body lengths) and has a distinct external morphology (darker grey dense fur with a thick, darker tail) and craniodental characters (braincase is rounded and elevated with weak lambdoidal ridges) in comparison to other close congeners. This is the first discovery of a shrew from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Considering the skeletal variation, the treeshrew species showed intraspecific variation depending upon their distribution in mainland and island ecosystems 74 . A recent molecular study also elucidates the biogeographic connection of smaller mammals in the AN archipelago with the Indo-Malayan and Sundaic realms 7 . The present mitogenome based phylogeny also manifested the close relationship of T. nicobarica with T. minor , T. tana , T. splendidula , and T. montana (distributed in Thailand, Peninsular and East Malaysia, Brunei Darussalam, Sumatra, and Indonesia) as compared with the widespread species T. belangeri known from South and Southeast Asia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the skeletal variation, the treeshrew species showed intraspecific variation depending upon their distribution in mainland and island ecosystems 74 . A recent molecular study also elucidates the biogeographic connection of smaller mammals in the AN archipelago with the Indo-Malayan and Sundaic realms 7 . The present mitogenome based phylogeny also manifested the close relationship of T. nicobarica with T. minor , T. tana , T. splendidula , and T. montana (distributed in Thailand, Peninsular and East Malaysia, Brunei Darussalam, Sumatra, and Indonesia) as compared with the widespread species T. belangeri known from South and Southeast Asia.…”
Section: Resultsmentioning
confidence: 99%
“…The AN archipelago was formed due to collision between the Indian Plate and Eurasian Plate which commenced about 50 million years ago and continues today 6 . Due to the distance of the archipelago from the mainland and different diachronic processes, this group of islands accommodates numerous unique elements of biodiversity 7 . This archipelago is a trenchant biogeographic entity that can be a model for evolutionary studies 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This plate tectonic also impelled multiple chances for animal oversea dispersal and biological connections between South and Southeast Asian countries (Kamalakannan et al. 2021 ). Nevertheless, the bathymetric study also evidenced a prominent connection between the AN archipelago to Sundaic Island by the well-developed seamounts and volcanic arc-chain (Rodolfo 1969 ; Tripathi et al.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that a total of 12 Crocidura species are known from India with a new discovery of Crocidura narcondamica from Andaman and Nicobar (AN) Archipelago (Kamalakannan et al. 2021 ). Among them, five species viz., C. andamanensis (Critically Endangered), C. hispida (Vulnerable), C. jenkinsi (Critically Endangered), C. narcondamica (Not Evaluated), and C. nicobarica (Critically Endangered) are endemic to the AN Archipelago (IUCN 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation